2011
DOI: 10.3109/08977194.2011.614949
|View full text |Cite
|
Sign up to set email alerts
|

JAKs go nuclear: Emerging role of nuclear JAK1 and JAK2 in gene expression and cell growth

Abstract: The four JAKS comprise a family of intracellular, non-receptor tyrosine kinases that first gained attention as signaling mediators of the type I and type II cytokine receptors. Subsequently, the JAKs were found to be involved in signaling downstream of the insulin receptor, a number of receptor tyrosine kinases, and certain G-protein coupled receptors. Although a number of cytoplasmic targets for the JAKs have been identified, their predominant action was found to be the phosphorylation and activation of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 84 publications
5
52
0
Order By: Relevance
“…We also demonstrated that both antibodies detect a single band at the molecular weight of JAK2 in Western blotting assays and showed that these antibodies only detect JAK2 in ␥2A cells transfected with JAK2 but not nontransfected cells within the same visual field. Importantly, these data are in keeping with the findings from multiple other independent groups that have also used IF to demonstrate nuclear JAK2 (reviewed in Qian et al 12 and Zouein et al 13 ).…”
Section: Insupporting
confidence: 67%
See 1 more Smart Citation
“…We also demonstrated that both antibodies detect a single band at the molecular weight of JAK2 in Western blotting assays and showed that these antibodies only detect JAK2 in ␥2A cells transfected with JAK2 but not nontransfected cells within the same visual field. Importantly, these data are in keeping with the findings from multiple other independent groups that have also used IF to demonstrate nuclear JAK2 (reviewed in Qian et al 12 and Zouein et al 13 ).…”
Section: Insupporting
confidence: 67%
“…12,13 We believe that much of the debate is likely related to methodologic differences, which are not easily resolved, and it seems highly likely that the amount of nuclear JAK2 varies in different cellular contexts. However, the current weight of evidence strongly supports a nuclear role for JAK2, a view that is consistent with emerging nuclear roles for a large number of kinases previously thought to function solely in the cytoplasm.…”
Section: Inmentioning
confidence: 99%
“…A JAK3-ERK (rather than a JAK3-STAT3) dependent signaling pathway has been implicated in the EGF-mediated induction of matrix metalloproteinase-9 in SKBR3 breast cancer cells (Kim et al, 2009). Alternatively, regulation of vimentin may bypass downstream signaling pathways, and occur via direct transcriptional and/or epigenetic regulation in the nucleus by one or more members of the JAK family, as has been described for JAK1 and JAK2 (Lobie et al, 1996;Zouein et al, 2011). To determine whether regulation of vimentin by either inhibitor may occur upstream of STAT3 activation at the level of the EGFR, we also assessed the effect of pharmacological inhibition on EGF-mediated EGFR phosphorylation.…”
Section: Sirna-mediated Silencing Of Jak Family Members Does Not Altementioning
confidence: 99%
“…However our understanding of JAK-STAT signaling, particularly its integration with the NF-B and cyclic AMP signaling pathways to regulate immune and inflammatory responses, remain incomplete. Moreover, new insights continue to emerge into roles both for nuclear-localised JAKs in chromatin remodeling and cell cycle regulation (Zouein et al, 2011) and links with Rho kinase that control actomyosin contractility, cell migration and even STAT3 activation (Sanz-Moreno et al, 2011). Consequently it is likely that the first wave of therapies targeting cytokine-activated JAK-STAT pathways is the beginning of several new approaches with which to treat the wide range of diseases in which they play a critical role.…”
Section: Resultsmentioning
confidence: 99%